ANALYSIS OF NUTRITIONAL STATUS OF TODDLERS AGED 12-60 MONTHS BASED ON ANTHROPOMETRIC MEASUREMENTS - Tri Endah Widi Lestari; Misrina Retnowati; Uti Lestari; Fatihah Wari Nurjanah (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
AbstractToddler nutritional status is an important indicator in assessing the success of early childhood growth and development. This study aims to describe the nutritional status of toddlers aged 12-60 months based on anthropometric measurements in the Kaligondang Community Health Center working area. The study used a descriptive analytical design with a total sampling technique on all toddlers aged 12-60 months totaling 374 respondents. The data used were secondary data including age, gender, weight, height, and nutritional status of toddlers. Nutritional status assessment was carried out using the weight for age (BW/A), height for age (H/A), and weight for height (BW/H) index based on WHO standards. The results showed that the majority of toddlers had normal nutritional status in the BW/A indicator of 322 children (86.1%), normal BW/A were 346 children (92.5%), and good nutritional BW/H were 313 children (83.7%). Nutritional problems still identified included 34 children (9.1%) being underweight, 28 children (7.5%) being stunted, 21 children (5.6%) being wasted, and 10 children (2.7%) being overweight. Most toddlers (237 children) experienced either a stable weight or a decrease in weight. It was concluded that the nutritional status of toddlers was generally good, but growth monitoring and nutritional interventions still need to be continuously improved in the local community.